When the thrill is gone [compact disc, unabridged] - Mosley, Walter (Mosley, Walter. Leonid McGill mysteries., 2011)
The economy has hit the private investigator business hard, and lately, Leonid McGill is getting job offers only from the criminals he's worked so hard to leave behind. So how can he say no to the beautiful young woman who walks into his office with a stack of cash? She's an artist, she tells him, who's escaped from poverty via marriage to a rich collector who keeps her on a stipend. But she says she fears for her life, and needs Leonid's help.